Demografik değişkenler bazında iş tatmini boyutlarında oluşan farklılıklar: Okmeydanı eğitim ve araştırma hastanesi personeline yönelik bir araştırma-The differences in the job satisfaction’s dimensions with respect to the demographic factors: a research - Mercanlıoğlu, A. Çiğdem (Öneri Dergisi, 2012)
Özet Kurumların etkinlik ve verimlilik boyutlarında başarılı olmalarının anahtarı, çalışanlarına verdiği değerdir. Bu çalışmada, Okmeydanı Eğitim ve Araştırma hastanesinde görevli, tesadüfi yöntemle seçilmiş 520 personelin, çalıştıkları poliklinik, yaş, cinsiyet, medeni durum, eğitim, kıdem ve mesleki deneyimleri ile, MSQ (Minnesota Satisfaction Questionnaire) Minnesota İş Tatmini Soru Formu ile elde edilen, iş tatmininin boyutlarında duydukları tatmin/tatminsizlik dereceleri arasında, istatistiksel olarak anlamlı farklılıkların tespitine yönelik bir araştırma yapılmıştır. Bulgular, çalışanların iş tatmininin, MSQ ile ortaya çıkan aktivite boyutu hariç, tüm boyutlarında, çalıştıkları polikliniklere göre anlamlı farklılık gösterirken, cinsiyet değişkeni 8 boyutta, medeni durum değişkeni 5 boyutta, yaş değişkeni 3 boyutta), meslek 4 boyutta, kıdem 2 boyutta ve son olarak mesleki deneyim 2 boyutta anlamlı farklılıklar göstermiştir. Abstract The key to a successful institution in efficiency and effectiveness, is the value given to employees. In this study, a survey based on MSQ (Minnesota Satisfaction Questionnaire), containing the sub-dimensions of job satisfaction has been conducted over Okmeydanı Educational and Research Hospital’s medical staff. The sample group of study was composed by randomly selecting 520 hospital staff. The aim was to determine the differences in the job satisfaction’s dimensions with respect to the demographic factors, including the employer clinic, age, sex, marital status, education, seniority and professional background. Findings have been significantly different except activity, from what was expected by the staff, in the dimensions that resulted from MSQ, with respect to the polyclinics they work in. There also have been differences in findings with respect to 8 dimensions of gender variables, 5 dimensions of marital status variables, 3 dimensions of age variables, 4 dimensions of profession, 2 dimensions of seniority and finally 2 dimensions of work experience.
Keywords: İş Tatmini, Hastane Çalışanları; Job Satisfaction, Health Care Staff